PENGARUH AKUNTABILITAS PENGELOLAAN KEUANGAN ALOKASI DANA DESA, KEBIJAKAN DESA, DAN KELEMBAGAAN DESA TERHADAP KESEJAHTERAAN MASYARAKAT: Studi Kasus Pada Desa Gubugklakah Kecamatan Poncokusumo Kabupaten Malang - Dura, Justita (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2016)
The purpose of this study examines the effect of financial management accountability allocation of village funds, village policy, institutional and villages on the welfare of the community. It is also conducted to determine whether the allocation of funds financial management accountability village, village policies, and village institutions jointly affect the welfare of the community. Respondents consisted of 55 women and 45 men from all walks of education and work different. All data is processed by multiple regression analysis with a look at the validity, realibiltas, and hypothesis testing by F test and t test. The results of this study indicate that accountability in financial management fund allocation village, village policies, and village institutions affect the welfare of the community, and accountability in financial management allocation of village funds, village policies, and institutional berpengaaruh village together for the welfare of society.